ANALISIS BEBAN GENERATOR TERHADAP NILAI HEAT RATE DAN EFISIENSI PLTU (STUDI OBSERVASIONAL DI PT. INDOCEMENT TUNGGAL PRAKARSA, Tbk P-12 TARJUN – KALIMANTAN SELATAN) - Muhammad Miftah Noor Rizca; Qomariyatus Sholehah; Sigit Siswanto (Scientific Journal of Mechanical Engineering Kinematika, 2018)
Heat rate is a measure of the reliability of a generating unit and as the amount of fuel energy required to produce 1 kWh of electrical energy. This study aimed to generator load analysis on the value of heat rate, specific coal consumption and the efficiency of the plant. Heat rate, specific coal consumption and power plant efficiency can be determined by knowing the proximate coal analysis, parameter data from the control room, determine the heat value of coal, power and efficiency of the auxiliary units, NPHR, SCC, the efficiency of the boiler, turbine and power plant. From the data processing are obtained graph generator load to NPHR, SCC and efficiency of the plant. From the calculations, the highest value NPHR of 3580.77 kcal / kWh when the load of 29.86 MW, the highest value of SCC of 0.60 kg / kWh when the load is 29.86 MW power plant and the highest efficiency of 33.54% when the load 47, 8 MW. So the higher the value of the generator load NPHR and SCC will be smaller, while efficient the power plant will increase.